NILAI DAN TIPE KONSUMEN RUMAH TANGGA DAN KAITANNYA DENGAN PERILAKU PEMBELIAN PRODUK MAKANAN KEMASAN - Ruwani, Ani; Retnaningsih, Retnaningsih; Simanjuntak, Megawati (Jurnal Ilmu Keluarga dan Konsumen, 2014)
Characteristics of consumers play an important role in determining the purchasing decision process, including the value and type of consumers. The purpose of this study was to analyze the effects of values and type of households on purchasing behavior of packaged foods in rural and urban areas of Bogor. This research used cross sectional design and involved 80 households who consumed packaged food; selected by random sampling at chosen study site. The result of the study revealed that households in urban area had better value of consumer than in rural area (p<0,01). Most of consumer both in urban and rural areas categorized as type of active consumer. The purchasing behavior in urban households was found higher than urban ones. Moreover, the research found a significant correlation among value of consumer, type of consumer, and purchasing behavior of packaged foods. Age of consumer, length of wife’s education, family size, and family income influenced significantly on purchasing behavior of packaged foods in rural and urban areas.